Sweet potato (Ipomoea batatas (L.) Lam): A new host for Brevicoryne brassicae (L.) and Myzus persicae (Sulzer) (Hemiptera: Aphididae) - e Castro, Bárbara Monteiro de Castro; Soares, Marcus Alvarenga; de Andrade Júnior, Valter Carvalho; Pires, Evaldo Martins (Comunicata Scientiae, 2013)
Sweet potato (Ipomoea batatas (L.) Lam.) is a plant potentially used as food in underdeveloped countries and although it is easy to be planted and managed, many factors, like insects, may limit its productivity. Usually, aphids attack cabbage (Brassica sylvestris (L.) Mill.) Mill.), negatively influencing on its development and survival. The aphid species observed were Brevicoryne brassicae and Myzus persicae (both Hemiptera: Aphididae). In this study was found that these species co-occur and show potential to cause damage also on sweet potato plants in Brazil. So, they have to be considered in Integrated Pest Management - IPM to sweet potato crop.